A Mutual Interest? Ethnography in Anthropology and Cultural Studies - McEachern, Charmaine (The Australian journal of anthropology, 1998)
Anthropology and cultural studies share a concern with ethnographic method. Cultural studies increasingly uses ethnography in its analyses of popular culture as it seeks to balance earlier preoccupations with text. Where cultural studies diverges from anthropology is in its encompassment within an oppositional paradigm which embeds a political agenda deep in its ethnographic work. This paper uses the area of media to explore the ways in which ethnography has been adopted and developed in cultural studies. Ethnographic focus has shifted interest in media from the text to the reception of media products. At the same time, the oppositional legacy from cultural studies' earliest days has tended to produce rather romanticised findings of a subaltern audience using media products to resist dominant cultural and political structures. It is suggested that anthropology should pay attention to cultural studies use of ethnographic method, first taking seriously the ground of popular culture as a challenge for anthropologists' more extended use of ethnography. But second, we should pay attention to the problem silences in cultural studies' ethnographies—silences like racism in audiences—since these may well have at least part of their basis in the method itself.